2013
DOI: 10.1155/2013/379839
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence Modulation by Small Bubbles in the Vertical Upward Channel Flow

Abstract: The liquid turbulence modulation by small bubbles was investigated detailedly in a vertical upward channel flow with a finite number of small bubbles with the developed Eulerian-Lagrangian method. Small bubbles are treated as pointwise spheres subject to gravity, drag, added mass, pressure gradient, lift, and wall lift forces. The momentum transfer between phases was realized through interphase forces. The present investigation shows that the liquid turbulence is intensified near the wall and is slightly weake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A number of these, such as the experiments presented by Hosokawa et al and the numerical simulations of Ervin and Tryggvason and Pang et al, focused on the dispersion of bubbles and their complex interactions with the turbulent flow structures. Pang et al investigation of a channel flow demonstrated that the liquid phase turbulence is intensified near the walls and slightly weakened in the central region due to bubble addition. Giusti et al used one‐way coupled numerical simulations to study the effect of the lift force on the behavior of nondeformable microbubbles dispersed in a turbulent vertical channel flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of these, such as the experiments presented by Hosokawa et al and the numerical simulations of Ervin and Tryggvason and Pang et al, focused on the dispersion of bubbles and their complex interactions with the turbulent flow structures. Pang et al investigation of a channel flow demonstrated that the liquid phase turbulence is intensified near the walls and slightly weakened in the central region due to bubble addition. Giusti et al used one‐way coupled numerical simulations to study the effect of the lift force on the behavior of nondeformable microbubbles dispersed in a turbulent vertical channel flow.…”
Section: Introductionmentioning
confidence: 99%
“…Although DNS resolves all the scales of a flow, and provides results comparable to those available from experimental studies, its computational cost means that it is still restricted to the simulation of relatively few bubbles, particularly when coupled with interface tracking techniques to resolve bubble motion, and low Reynolds number flows. Even when coupled to a Lagrangian methodology that allowed the tracking of significant numbers of bubbles (approximately several hundred thousands), DNS studies in closed ducts have been mostly limited to 150–200 shear Reynolds number flows . Instead LES, where the large scales of turbulent motion are resolved while the subgrid turbulent scales and their effect on the mean flow are modeled, allows complex flows with industrial relevance to be predicted more readily.…”
Section: Introductionmentioning
confidence: 99%
“…Prediction of population balance approaches and the accuracy of coalescence and breakup models strongly depends on turbulence in the continuous field and the turbulence modelling approach used to predict it [9]. In previous studies, turbulence modulation in bubbly flows due to the dispersed bubbles has been widely discussed and analysed by comparing turbulence statistics for different bubble sizes and properties [13][14][15]. However, detailed analysis of the impact of turbulence on four-way coupled simulations and predictions of the models used to account for bubble coalescence and breakup have rarely been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental investigations had been conducted by researchers [4][5][6][7][8][9]. Numerical studies had also been carried out by researchers [10][11][12][13][14][15][16][17][18]. Kim et al [19] conducted theoretical analyses on the liquid turbulence modulation by microbubbles.…”
Section: Introductionmentioning
confidence: 99%